Kritik Karl Marx terhadap Manajemen Pendidikan Islam: Perspektif Sosiologi Kritis - Muhamad Iqbal; Silfia Hanani; Nur Indri Yani Harahap; Andy Riski Pratama (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
This research analyzes Karl Marx's critical views on Islamic education management through the perspective of critical sociology and the basic concepts of Marxism. This study aims to analyze Karl Marx's critical views on Islamic education management through the lens of critical sociology. Karl Marx, a critical theorist and adherent of the historical materialist view, has made major contributions to the understanding of social inequality and structural injustice in society. The research method involves a literature study that examines relevant text and literature sources. The research results show that the Marxist view critically identifies issues of inequality, social exclusion, and the influence of capitalism in the management of Islamic education. Although this research provides a valuable theoretical contribution in understanding Islamic education management from a critical sociological perspective, further research and empirical research is still needed to explore its concrete impact. These findings emphasize the importance of considering structural factors and inequality in efforts to increase inclusiveness and justice in the Islamic education system.